A review on major aspects of dengue - HARDEEP KAUR; REEMA SHARMA (International Journal of Pharma and Bio Sciences, 2019)
Dengue is a viral illness caused by a RNA virus belonging to family Flaviviridae. This virus is further classified into four distinct serotypes. Dengue is spread by the bite of mosquito - Aedes aegypti. Symptoms of Dengue from moderate fever to extreme conditions such as dengue hemorrhagic fever and shock syndrome, which have significant distress and mortality. The disease has a huge percentage of clinically asymptomatic cases observed till now. Some common symptoms are frontal headache, fever, and severe musculoskeletal pain. Dengue is also responsible for many highly complex pathophysiological, economical and ecological problems. Dengvaxia is the first vaccine approved by FDA for the prevention of dengue disease caused by all serotypes of dengue virus Preventive measures should be taken to avoid disease extent and diminish epidemic flash up as it has turned out to be a major public health problem.